The social function of the Committees for the Defense of the Revolution in Cuba. Theoretical analysis (Islas, 2022)
ABSTRACT: Introducción: The social function of the Committees for the Defense of the Revolution (CDR), distinguishes the essence of the organization, in correspondence with the demands of the VIII Congress of the Communist Party of Cuba (PCC) to consolidate a prosperous and sustainable socialism from the community. The research, which is the result of a doctoral thesis, aims to examine the historical scope and his main contributions in Cuba, from the revolutionary thought of Fidel Castro. Methods: The dialectical-materialist, analysis-synthesis, historical and logical methods were use, the main results being found in the study of the historical foundations of the cederist social function and its materialization in the community practice. Results: The results show, based on the work tendencies, the role it plays and the way it relates to other factors of its social space, as well as the relationship with society as a whole. From the theoretical analysis, the CDRs are enriched from the recognition and identification of the essential periods, where the main institutional, normative, ideological changes, political relations of the country and their influence on the way of participation of the people as a massive subject of power take place. Conclusions: In the analysis of the tendencies of the CDR work systems the social function expresses the interdependence relations of the elements that compose the society. In the study of the historical stages, it is considered that the CDR strengthen their participation from experiences of work in the community, which is developed with a perspective of improvement, from articulating and harmonizing the presence of the people in the projection and execution of community strategies to satisfy the material and spiritual needs of Cuban society.
Keywords: Social function; community organization; Committees for the Defense of the Revolution